2022
DOI: 10.1002/ece3.9081
|View full text |Cite
|
Sign up to set email alerts
|

Decadal abundance patterns in an isolated urban reptile assemblage: Monitoring under a changing climate

Abstract: Determine seasonal, annual, and decadal patterns of abundance in reptile species and assemblages occupying central Bold Park (~338 ha), an isolated urban bushland remnant in Perth, Southwestern Australia. Fenced pitfall trapping in four sampling sites, representing different habitats and fire history, over the primary reptile activity period for 35 consecutive years with over 17,000 individuals captured during 3300 days of sampling; the trapping regime was modified for the last 28 years. Sampling occurred in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…However, Ryan et al [75], discovered that reptiles in the Los Pino Mountains in New Mexico, US, preferred foraging in sunny microhabitats following rainfall events and shaded habitats during dry periods. Further, increased precipitation is also thought to increase reproduction by some reptiles [59]. Whilst our study contrasts in both habitat conditions and species identities to those mentioned above, our results likely point to species-specific responses to rain, as well the difficulties in disentangling the effects of occupancy and activity on reptile detections.…”
Section: Plos Onecontrasting
confidence: 66%
See 1 more Smart Citation
“…However, Ryan et al [75], discovered that reptiles in the Los Pino Mountains in New Mexico, US, preferred foraging in sunny microhabitats following rainfall events and shaded habitats during dry periods. Further, increased precipitation is also thought to increase reproduction by some reptiles [59]. Whilst our study contrasts in both habitat conditions and species identities to those mentioned above, our results likely point to species-specific responses to rain, as well the difficulties in disentangling the effects of occupancy and activity on reptile detections.…”
Section: Plos Onecontrasting
confidence: 66%
“…This enabled us to associate climate data in the season in which surveys were taken. We also calculated mean monthly precipitation for the year preceding the survey, as reptiles are known to increase reproduction following higher than average rainfall [59].…”
Section: Plos Onementioning
confidence: 99%
“…The impacts of climate change on reptiles and interactions with fire, are poorly understood and require future study. How et al (2022) analysed a 35-year dataset of reptiles in Banksia woodlands near to our study site and found that abundance was significantly correlated with preceding rainfall. They found only limited community compositional change due to annual rainfall variation.…”
Section: Discussionmentioning
confidence: 99%
“…These altered fire regimes combine with other disturbances, such as edge effects (Urbina- Cardona et al 2006;Garden et al 2007;McAlpine et al 2015), to further alter vegetation structure (Ibanez et al 2017;Gomes et al 2022). In combination, these pressures, along with a changing climate (How et al 2022), have the potential to strongly influence post-fire responses of reptiles in urban remnants. However, whether post-fire responses differ between remnants and contiguous vegetation remains poorly understood and the ecological mechanisms behind any potential differences, even less well understood.…”
Section: Introductionmentioning
confidence: 99%